2007
DOI: 10.1021/bm070083c
|View full text |Cite
|
Sign up to set email alerts
|

Novel Preparation Method for Poly(l-lactide)-Based Block Copolymers:  Extended Chain Crystallites as a Solid-State Macro-Coinitiator

Abstract: A novel synthetic method for poly(L-lactide) (PLLA)-based diblock copolymers was developed by the use of PLLA extended chain crystallites (or crystalline residues) as a solid-state macro-coinitiator. In this study, we showed one example, i.e., a synthesis of diblock copolymer composed of a crystalline PLLA chain and an amorphous poly(DL-lactide) chain by ring-opening polymerization of DL-lactide initiated with stannous octoate (i.e., tin(II) 2-ethylhexanoate) in the presence of PLLA extended chain crystallites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Also, Tsuji et al [68] prepared block copolymers by ringopening polymerization of DLLA coinitiated with PLLA crystalline residues (or extended-chain crystallites) prepared by NHD of crystallized PLLA films. Extended-chain crystallites can act as a macrocoinitiator because they have many hydroxyl groups as terminal groups on their surface.…”
Section: Formation Of Reactive Sites On Surfacementioning
confidence: 99%
“…Also, Tsuji et al [68] prepared block copolymers by ringopening polymerization of DLLA coinitiated with PLLA crystalline residues (or extended-chain crystallites) prepared by NHD of crystallized PLLA films. Extended-chain crystallites can act as a macrocoinitiator because they have many hydroxyl groups as terminal groups on their surface.…”
Section: Formation Of Reactive Sites On Surfacementioning
confidence: 99%
“…Recently, a novel synthetic method was developed by the use of poly( L ‐lactide) (PLLA) extended chains resulting from the hydrolytic degradation of PLLA crystallized films. Extended chains are anticipated to act as a initiator system with Sn(Oct) 2 because they have many hydroxyl groups 18…”
Section: Introductionmentioning
confidence: 99%
“…The resolution powers for the FTIR spectra were 2 cm −1 . Gel permeation chromatography and WAXD were carried out by using previously reported procedures 23, 28. WAXD showed that PGA crystallites with orthorhombic unit cells29, 30 are formed at a PGA content of at least above 3 wt.‐% in melt‐quenched PLLA/PGA specimens and that PLLA and PGA crystallize separately to form their respective crystallites.…”
Section: Experimental Partmentioning
confidence: 99%